"You Forget to Apply It to Staff": A Compassion-Focused Group for Mental Health Inpatient Staff. An Exploration of the Barriers to Attendance. (9th September 2022) - Drobinska, Kamila; Oakley, David; Way, Carrie; Jackson, Mike
Abstract: This study explored the feasibility and acceptability of an experiential compassion-focused group intervention for mental health inpatient staff. Findings demonstrated that although participants found sessions enjoyable, and reported a number of benefits, the group attrition was high. Semi-structured interviews were conducted to explore issues related to group dropout. Thematic analysis highlighted overarching systemic challenges to attendance, and five key themes emerged: The Nature of the Ward; Slowing Down Is Not Allowed; It is Not in Our Nature; Guilt & Threat; We Are Not Important. Clinical implications, limitations and practice recommendations to support group attendance are also addressed.